General practitioners' justifications for therapeutic inertia in cardiovascular prevention: an empirically grounded typology. Issue 5 (13th May 2016) - Lebeau, Jean-Pierre; Cadwallader, Jean-Sébastien; Vaillant-Roussel, Hélène; Pouchain, Denis; Yaouanc, Virginie; Aubin-Auger, Isabelle; Mercier, Alain; Rusch, Emmanuel; Remmen, Roy; Vermeire, Etienne; Hendrickx, Kristin
Abstract : Objective: To construct a typology of general practitioners' (GPs) responses regarding their justification of therapeutic inertia in cardiovascular primary prevention for high-risk patients with hypertension. Design: Empirically grounded construction of typology. Types were defined by attributes derived from the qualitative analysis of GPs' reported reasons for inaction. Participants: 256 GPs randomised in the intervention group of a cluster randomised controlled trial. Setting: GPs members of 23 French Regional Colleges of Teachers in General Practice, included in the EffectS of a multifaceted intervention on CArdiovascular risk factors in high-risk hyPErtensive patients (ESCAPE) trial. Data collection and analysis: The database consisted of 2638 written responses given by the GPs to an open-ended question asking for the reasons why drug treatment was not changed as suggested by the national guidelines. All answers were coded using constant comparison analysis. A matrix analysis of codes per GP allowed the construction of a response typology, where types were defined by codes as attributes. Initial coding and definition of types were performed independently by two teams. Results: Initial coding resulted in a list of 69 codes in the final codebook, representing 4764 coded references in the question responses. A typology including seven types was constructed. 100 GPs were allocated to one and only one of these types, while 25 GPs did not provide enough data to allow classification. Types (numbers of GPs allocated) were: 'optimists' (28), 'negotiators' (20), 'checkers' (15), 'contextualisers' (13), 'cautious' (11), 'rounders' (8) and 'scientists' (5). For the 36 GPs that provided 50 or more coded references, analysis of the code evolution over time and across patients showed a consistent belonging to the initial type for any given GP. Conclusion: This typology could provide GPs with some insight into their general ways of considering changes in the treatment/management of cardiovascular risk factors and guide design of specific physician-centred interventions to reduce inappropriate inaction. Trial registration number: NCT00348855.